Overweight and prognosis in triple-negative breast cancer patients: a systematic review and meta-analysis - Sixten Harborg (Nature Portfolio, 2021)
Abstract We conducted a systematic review and meta-analysis investigating the association between overweight and outcome in triple-negative breast cancer (TNBC) patients. We searched PubMed and Embase using variations of the search terms triple-negative breast cancer (population), overweight and/or obesity (exposure), and prognosis (outcome). Based on the World Health Organization guidelines for defining overweight, we included longitudinal observational studies, which utilized survival statistics with hazard ratios (HRs) in our analysis. The included studies measured body mass index at the time of diagnosis of TNBC and reported disease-free survival and/or overall survival. Study quality was assessed with the Newcastle-Ottawa Scale and study data were extracted using the Meta-analysis of Observational Studies in Epidemiology (MOOSE) checklist, independently by two authors. Random-effects models were used to combine the effect sizes (HRs), and the results were evaluated and adjusted for possible publication bias. Thirteen studies of 8,944 TNBC patients were included. The meta-analysis showed that overweight was associated with both shorter disease-free survival (HR = 1.26; 95%CI: 1.09–1.46) and shorter overall survival (HR = 1.29; 95%CI: 1.11c1.51) compared to normal-weight. Additionally, our Bayesian meta-analyses suggest that overweight individuals are 7.4 and 9.9 times more likely to have shorter disease-free survival and overall survival, respectively. In conclusion, the available data suggest that overweight is associated with shorter disease-free and overall survival among TNBC patients. The results should be interpreted with caution due to possible publication bias.